Composition‐dependent underwater adhesion of catechol‐bearing hydrogels. Issue 11 (8th September 2016) - Wu, Haosheng; Sariola, Veikko; Zhao, Jingsi; Ding, Hangjun; Sitti, Metin; Bettinger, Christopher J
Abstract: Interfacial adhesion‐mediated transfer printing processes can integrate functional electronic microstructures with polymeric substrates that are bendable and stretchable. Transfer printing has also been extended to catechol‐bearing adhesive hydrogels. This study presents indentation adhesion tests between catechol‐bearing hydrogel substrates with catechol concentrations varying from 0 to 10% (mol/mol) and thin‐film materials commonly used in microelectronic fabrication including polymers, noble metals and oxides. The results indicate that the interfacial adhesion of catechol‐bearing hydrogels is positively correlated with the concentration of catechol‐bearing monomers as well as the retraction velocity during transfer printing. This study can inform transfer printing processes for microfabricated structures to compliant hydrated substrates such as hygroscopic monomers, mesoporous polymer networks and hydrogels. © 2016 Society of Chemical Industry Abstract : This study presents indentation adhesion tests between catechol‐bearing hydrogel substrates with catechol concentrations varying from 0 to 10% (mol/mol) and thin‐film materials commonly used in microelectronic fabrication including polymers, noble metals and oxides.